Intentions for risk‐reducing surgery among high‐risk women referred for BRCA1/BRCA2 genetic counseling. Issue 1 (17th May 2014) - Tong, Angie; Kelly, Scott; Nusbaum, Rachel; Graves, Kristi; Peshkin, Beth N.; Valdimarsdottir, Heiddis B.; Wood, Marie; McKinnon, Wendy; Garber, Judy; McCormick, Shelley R.; Jandorf, Lina; Schwartz, Marc D.
Abstract Objective Genetic testing for breast and ovarian cancer susceptibility is now part of routine clinical practice. Although rates of risk‐reducing surgery following genetic testing have been increasing, little is known about attitudes toward risk‐reducing surgery in women prior to genetic counseling and testing. This study examines correlates of patient intentions to undergo risk‐reducing mastectomy (RRM) and risk‐reducing oophorectomy (RRO). Methods Participants were 696 women, ages 21–85, who sought breast cancer gene 1 and 2 (BRCA1/2) genetic counseling and had at least a 10% risk of carrying a mutation. The sample included women who were affected with breast or ovarian cancer and unaffected women with a known familial BRCA1/2 mutation. Participants completed a precounseling telephone questionnaire. Results Prior to receiving genetic counseling, 23.3% of participants were considering RRM and 42.5% were considering RRO. Variables that were independently associated with RRM intentions were cancer‐specific distress (OR = 1.14, 95% CI = 1.03–1.26), perceived risk of breast cancer (OR = 1.16, 95% CI = 1.05–1.28), education (OR = 1.76, 95% CI = 1.03–2.99), and age (OR = 0.96, 95% CI = 0.95–0.98). Predictors of RRO intentions were perceived risk for ovarian cancer (OR = 1.25, 95% CI = 1.14–1.37), perceived risk of carrying a BRCA1/2 mutation (OR = 1.74, 95% CI = 1.15–2.62), marital status (OR = 1.92, 95% CI = 1.34–2.76), and age (OR = 1.02, 95% CI = 1.00–1.03). Conclusions Because precounseling intentions predict subsequent risk‐reducing surgery decisions, this study identified patient factors associated with surgical intentions. These factors reinforce the critical role for pretest genetic counseling in communicating accurate risk estimates and management options, and addressing psychosocial concerns, to facilitate informed decision making regarding RRM and RRO. Copyright © 2014 John Wiley & Sons, Ltd.